Clinical value of extended pelvic lymph node dissection in patients subjected to radical prostatectomy - Dobruch, Jakub (Termedia Publishing House, 2014)
INTRODUCTION: Extended pelvic lymph node dissection (ePLND) is advised to complement radical prostatectomy (RP) in intermediate and high risk prostate cancer patients. AIM: To assess the risk of nodal involvement in patients subjected to laparoscopic radical prostatectomy and to characterize the group of patients with lymph node (LN) metastases. MATERIAL AND METHODS: Data of patients subjected to laparoscopic radical prostatectomy with ePLND between February 2011 and June 2013 were analyzed. The LN that were removed included presacral nodes, common, external and internal iliac nodes and obturator ones. RESULTS: Mean number of removed LNs was 19. Metastases within LN were found in 13 (16.6%) patients. In comparison to those without LN involvement, patients who were found to have LN metastases had a greater number of positive biopsy cores (3.7 vs. 5.3, p < 0.01), maximum percentage of cancer in biopsy core (47.0 vs. 67.6, p < 0.01), greater biopsy and specimen Gleason scores (7.0 vs. 7.7 and 7.0 vs. 7.8) and more frequently advanced clinical and pathological stage. The most frequent landing sites of prostate cancer were obturator and presacral nodes (100% and 38%). Eleven patients (85%) among those with positive LN had locally advanced disease. CONCLUSIONS: The risk of LN metastases in intermediate and high risk prostate cancer patients is significant. Therefore, if radical prostatectomy is chosen, ePLND should be performed. The majority of patients with involvement of pelvic LN have locally advanced disease which would refer them to adjuvant radiation if managed without nodal dissection.